Age of dementia diagnosis in community dwelling bilingual and monolingual Hispanic Americans. (May 2015) - Lawton, Deborah M.; Gasquoine, Philip G.; Weimer, Amy A.
Abstract: Bilingualism has been reported to delay the age of retrospective report of first symptom in dementia. This study determined if the age of clinically diagnosed Alzheimer's disease and vascular dementia occurred later for bilingual than monolingual, immigrant and U.S. born, Hispanic Americans. It involved a secondary analysis of the subset of 81 bi/monolingual dementia cases identified at yearly follow-up (1998 through 2008) using neuropsychological test results and objective diagnostic criteria from the Sacramento Area Latino Study on Aging that involved a random sampling of community dwelling Hispanic Americans ( N  = 1789). Age of dementia diagnosis was analyzed in a 2 × 2 (bi/monolingualism × immigrant/U.S. born) ANOVA that space revealed both main effects and the interaction were non-significant. Mean age of dementia diagnosis was descriptively (but not significantly) higher in the monolingual ( M  = 81.10 years) than the bilingual ( M  = 79.31) group. Overall, bilingual dementia cases were significantly better educated than monolinguals, but U.S. born bilinguals and monolinguals did not differ significantly in education. Delays in dementia symptomatology pertaining to bilingualism are less likely to be found in studies: (a) that use age of clinical diagnosis vs. retrospective report of first dementia symptom as the dependent variable; and (b) involve clinical cases derived from community samples rather than referrals to specialist memory clinics.